Effect of Sodium Alginate-Carrageenan Concentration in Rifampicin Pulmospheres on Physical Characteristics, Release, and Anti-Tuberculosis Activity - Liempepas, Angelika; Rahmadi, Mahardian; Ifadotunnikmah, Farida; Hariyadi, Dewi Melani (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Pulmonary tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis, which mostly attacks the lungs, but can also affect other organs. Tuberculosis is one of the biggest health problems worldwide. Conventional oral rifampicin preparations have several limitations, such as poor bioavailability, low solubility, and drug instability in the gastrointestinal fluid. Only a small portion of the tuberculosis drug can reach the alveoli, the main target of the tuberculosis drug. Drug delivery Systems are one of the solutions to this problem. They are a formulation or system that can mediate the delivery of therapeutic substances in the body to increase therapeutic effects, reduce drug side effects, increase bioavailability, and improve patient compliance. Pulmonary drug delivery requires a small dose and particle size, so microspheres are selected for lung delivery. This research aims to study the effect of sodium alginate concentration and carrageenan (0.75%, 1%, 1.25%) with a ratio of 1:1 on physical characteristics, in vitro release, and anti-tuberculosis activity. Preparation of Rifampicin Sodium Alginate-Carageenan Pulmospheres with Ionotropic Gelation-Aerosolization. Pulmospheres were evaluated for entrapment efficiency, morphology, yield, particle size, drug loading, in vitro release, and Mycobacterium smegmatis activity. Increasing concentrations of sodium alginate and carrageenan produce rifampicin pulmospheres with good physical characteristics, increase rifampicin release, and result in inhibitory activity against Mycobacterium smegmatis